Suitability ofSurfactants in Enhanced Oil Recovery - Ahmad Zaki, Azfarizal (Universiti Teknologi Petronas, 2004)
As the EOR technology is yet to be introduced in Malaysia, an initial study have to be started to determine its suitability. Thus, chemical EOR or chemical flooding, as a possible candidate of EOR method to be run in Malaysia, has to be studied its compatibility with the Malaysia oil field conditions. This project intended to study suitability of surfactant with Malaysian crude oil and sea water through analyzing certain parameter in EOR. In this project, the interaction of selected surfactant with water mixture and crude oil from Malaysian oil field is determined through interfacial tension (IFT) analysis. Instead of that, the suitable polymer compatible with the Malaysia reservoir need to be determined to be used along with the selected surfactant. The analysis began with preparation of water blends and crude oil, before the test on polymer and surfactant is done. The main technique used in this project is the analysis of IFT using spinning drop tensiometer. The final surfactant candidate also undergoes phase behavior test to determine the interaction between surfactant solution with crude oil at different water mixtures and surfactant concentrations. From the study, the surfactant that has the best performance with Malaysia fluid condition is Sample 6-79 as it shows the lowest range of IFT at all testing condition. Apart from that, the polymer Superfloc BD319 have shown the best results compared to the other polymer tested and have the potential use with the surfactant to be applied in the chemical flooding in Malaysia.